Attitudes and perceptions of people with a learning disability, family carers, and paid care workers towards cancer screening programmes in the United Kingdom: A qualitative systematic review and meta‐aggregation. Issue 3 (29th December 2019) - Byrnes, Kate; Hamilton, Sharon; McGeechan, Grant J.; O'Malley, Claire; Mankelow, Jagjit; Giles, Emma L.
Abstract: Objective: Evidence suggests that people with a learning disability (PwLD) are less likely to attend cancer screening than the general population in the United Kingdom. The aim of this systematic review was to identify and synthesise qualitative studies reporting the attitudes and opinions of PwLD, family carers, and paid care workers towards national cancer screening programmes . Methods: Five electronic and two grey literature databases were searched. Fourteen thousand eight hundred forty‐six papers were reviewed against predetermined inclusion criteria. Included papers were critically appraised. Findings were synthesised using meta‐aggregation. Results: Eleven papers met the inclusion criteria, all related to cervical and breast screening. No papers were related to colorectal cancer screening. Findings were clustered into four synthesised findings: (1) supporting women with a learning disability (WwLD) to attend screening, (2) WwLD's awareness of screening and their psychophysical experiences, 3) professional practice barriers including the need for multidisciplinary working and an understanding of the needs of WwLD, and (4) approaches to improve the uptake of cervical and breast cancer screening. The synthesis highlights the significance of WwLD having support to understand the importance of screening to be able to make an informed choice about attending. Conclusions: WwLD may not attend cancer screening due to fear, concerns over pain, and the potential influence of family carers and paid care workers. The review identified practical mechanisms which could help WwLD attend screening. Future research should focus on identifying potential barriers and facilitators as a proactive measure to promote colorectal cancer screening.